Foreign states as participants in a civil process - Muidenova, A.K.; Aitimov, B.Zh. (Bulletin of the Karaganda University “Law Series”, 2024)
As the investment climate in our country improves, the influx of foreign investments into the national economy also increases. In this regard, it is necessary to constantly improve civil procedural legislation involving foreign states. Issues related to improving civil proceedings with the participation of foreign states must be thoroughly assessed and scientifically substantiated, taking into account all possible scenarios. The purpose of the research is to analyze the peculiarities of foreign states as participants in civil proceedings according to civil procedural legislation and to provide legislative proposals for its improvement. The research compares the current norms regulating civil processes involving foreign states with the legislations of Russia, Uzbekistan, and Kyrgyzstan, while also reviewing the works of foreign and domestic scholars on this topic. Civil procedural norms regarding cases involving foreign states were analyzed, and appropriate legislative recommendations were formulated. The relevance of the topic is determined by the recent increase in economic integration with foreign states and the growth of civil relations involving foreign entities in the Republic of Kazakhstan under the conditions of a market economy. As a result of the study, the foundations for foreign states to exercise jurisdictional immunity under the civil procedural legislation of the Republic of Kazakhstan were identified, and it was confirmed that all conditions for limiting judicial immunity are clearly defined. Nevertheless, the role of foreign states as full participants in civil proceedings still requires clarification.